The Use of Information Technology System for Risk Control at a Sharia Cooperative - Saiful Bakhri; Nur Asnawi; Ahmad Djalaluddin (Shirkah: Journal of Economics and Business, 2023)
The use of technology plays an unnegotiable role in the risk control of sharia cooperatives. Because almost all sharia cooperatives lack proper information technology systems, many cooperatives are unable to recognize the risks, particularly due to a lack of liquidity as well as a lack of managerial supervision and control over operational transactions carried out by officers. An improvement in the current information technology systems can replace these roles. This study analyzes the use of information technology systems in the financing, liquidity, and sharia compliance risk control in the BMT UGT Nusantara Cooperative, located in Pasuruan East Java. This descriptive qualitative involves informants of administrators, supervisors, managers, branch heads, and IT providers. With automaticÂ notification system, applicant screening, application adjusting policies and regulation, this study indicates that upgrading information technology systems are critical to minimizing risks and lowering the ratio of non-performing financing. It also eases the applicants as well as the institution in the process of application and screening as well as an installment payment.